Middle Managers' Role in Corporate Entrepreneurship: Pessimistic or Optimistic Future. - Mistal, Vishal (2008)
Research has advocated the role of middle managers in successful corporate entrepreneurship. However, considerable debate exists in the wider strategic management literature about the role of middle managers and the specific ways in which they add value to or detract value from firm activities. In response, a detailed study of conditions enabling and disabling Corporate Entrepreneurship is made and an examination is carried out to assess how middle managers might enable or disable Corporate Entrepreneurship therein. It is found that middle managers are less important to Corporate Entrepreneurship to the structures and processes of the firm and how this directs autonomous or controlled behavior by employees in pursuit of Corporate Entrepreneurship. The findings reveal implications for top management flat structure and hierarchical structure organization while managing corporate entrepreneurship. Implications and conclusions from these findings are drawn for multiple stakeholders.